2019
DOI: 10.1042/cs20190111
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis and lipoproteins are key factors in late immune recovery in successfully treated HIV-infected patients

Abstract: The immunological, biochemical and molecular mechanisms associated with poor immune recovery are far from known, and metabolomic profiling offers additional value to traditional soluble markers. Here, we present novel and relevant data that could contribute to better understanding of the molecular mechanisms preceding a discordant response and HIV progression under suppressive combined antiretroviral therapy (cART). Integrated data from nuclear magnetic resonance (NMR)-based lipoprotein profiles, mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Consistent with our data, rs1494558 -A was related to new-onset diabetes development after transplantation, playing an important role in the homeostasis of Treg cells, the regulatory T cells that play a major role in controlling immune responses to self-antigens 33 . Notice that diabetes is a metabolic complication associated with increased cardiovascular disease risk, a non-AIDS-defining clinical event, and INRs are associated with worse long-term clinical prognosis, including a higher risk of progression toward non-AIDS-defining clinical events 34 . Later, the rs1494558 -A and rs1494555 -C genotypes were also associated with an increased risk of acute and chronic graft versus host disease after allogeneic hematopoietic cell transplantation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our data, rs1494558 -A was related to new-onset diabetes development after transplantation, playing an important role in the homeostasis of Treg cells, the regulatory T cells that play a major role in controlling immune responses to self-antigens 33 . Notice that diabetes is a metabolic complication associated with increased cardiovascular disease risk, a non-AIDS-defining clinical event, and INRs are associated with worse long-term clinical prognosis, including a higher risk of progression toward non-AIDS-defining clinical events 34 . Later, the rs1494558 -A and rs1494555 -C genotypes were also associated with an increased risk of acute and chronic graft versus host disease after allogeneic hematopoietic cell transplantation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Total CD4 + T-cell count > 250 cells/µl at 2-3 years after ART initiation, with an undetectable plasma VL. 23,170,180,245 Increase in the CD4 + T-cell count < 50 cells/µl from baseline at 1 year after ART initiation, with plasma HIV RNA < 40 copies/ml.…”
Section: Definition Of "Immunological Nonresponder" Definition Of "Immentioning
confidence: 99%
“…A more recent study from the Netherlands using targeted metabolites of biogenic amine, lipids, oxylipins, and oxidative stress showed minimal change after one year of ART [10]. Another untargeted metabolomics study from Spain indicated that glutaminolysis and lipoproteins are vital factors in slow immune recovery at 96 weeks of antiretroviral therapy [13]. Thus, PLHIV on suppressive ART have an increased risk of metabolomic disorders that can increase their risk of age-related diseases.…”
Section: Introductionmentioning
confidence: 99%